From primary agents to corporate actors: A morphogenetic analysis of student becoming through a university residential education and support programme during the COVID-19 pandemic (Journal of Student Affairs in Africa, 2026)
This article explores how the educational becoming of first-generation students was catalysed through their participation in a residential education and support programme (RESP) at Stellenbosch University during the COVID-19 pandemic. Drawing on Margaret Archer’s morphogenetic theory, the article traces students’ transformation from primary agents to corporate actors, mapping their evolving identities through structural conditioning, sociocultural interaction, and agentic elaboration. Based on a longitudinal ethnographic case study of six students who remained in residence during lockdown, the research examines how the RESP, rooted in dialogical engagement, care ethics, and humanising pedagogy, functioned as a generative space for collective reflexivity, relational learning, and the activation of student agency. The findings demonstrate that the RESP enabled students to reconfigure their sense of self, assume leadership roles, and reshape institutional spaces from the margins. This study contributes to scholarship on intentional residential education practices, student subjectivity, pedagogies of care, and higher education transformation in post-apartheid South Africa. It offers insights into how inclusive and relational educational practices can foster student agency and social transformation, particularly for the historically marginalised within higher education.
Keywords: COVID-19 pandemic; residential education and support programme (RESP); morphogenesis; agency; epistemic virtues